PENCEGAHAN DAN TATALAKSANA DEKUBITUS PADA GERIATRI - Iin Novita Nurhidayati Mahmuda (Universitas Muhamadiyah Surakarta, 2019)
Decubitus ulcer or pressure sore is a serious morbidity in elderly patients. The incidence of pressure sores in geriatric patients is 11%. Population at 70-75 of their aged had a two-fold risk higher for suffering decubitus ulcers compared with 55-69 years of aged people. The highest incidence is in group of 80-84 years old peole. Studies has found 95% of cases are preventable. Prevention efforts have already proven to be more effective and cost effective than treatment. Prevention efforts include mobilization, skin care, fulfillment of fluids and adequate nutrition, the use of tools / aids for body movement, environmental regulation of health care and education. Treatment of decubitus ulcers by administering topical material, systemic drugs or surgery should be done as early as possible. Keyword: decubitus ulcer, geriatric patients, prevention, treatment